Implementasi gerakan literasi sekolah (GLS) di sekolah dasar - Ariani, Skolastika Ellen Mada; Sukarno, Sukarno; Chumdari, Chumdari (Universitas Sebelas Maret, 2020)
The reserach aims to: (1) describe the implementation of the School Literacy Program and (2) describe the efforts of the school to support the implementation of School Literacy Program. This research uses a qualitative approach with case study methods. The research subjects involved were fourth grade students of Bumi 1 Elementary School, Surakarta. Research data collection techniques using observation and interviews. The validity of research data uses triangulation techniques. Data were analyzed using an interactive model, consisting of data reduction, data presentation, and drawing conclusions. The results showed that the implementation of School Literacy Program at Bumi 1 Elementary School had been scheduled on a Monday to Friday basis for approximately 30 minutes every day. The implementation of School Literacy Program includes reading literacy, numeracy literacy, cultural literacy, and religious literacy. The conclusions of this research are: (1) the implementation of the School Literacy Program program in Bumi 1 Elementary School has been running on a routine daily schedule; (2) The efforts of the school in implementing School Literacy Program involve the efforts of principals and teachers to increase student interest and activity in School Literacy Program.